Trigeminal Neuralgia TRPM8 Mutation: Enhanced Activation, Basal [Ca2+]i and Menthol Response. (February 2021) - Gualdani, Roberta; Yuan, Jun-Hui; Effraim, Philip R.; Di Stefano, Giulia; Truini, Andrea; Cruccu, Giorgio; Dib-Hajj, Sulayman D.; Gailly, Philippe; Waxman, Stephen G.
Abstract : Objective: To assess the functional effects of a variant, c.89 G > A (p.Arg30Gln), in the transient receptor potential melastatin 8 (TRPM8) cold-sensing, nonselective cation channel, which we have previously identified in a patient with familial trigeminal neuralgia. Methods: We carried out Ca 2+ imaging and whole-cell patch-clamp recording. Results: The TRPM8 mutation enhances channel activation, increases basal current amplitude and intracellular [Ca 2+ ] in cells carrying the mutant channel, and enhances the response to menthol. Conclusions: We propose that Arg30Gln confers gain-of-function attributes on TRPM8, which contribute to pathogenesis of trigeminal neuralgia in patients carrying this mutation.